Challenges of Nursing Students during Covid-19 Pandemic - Muniyandi. S (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2023)
This study focuses on understanding the challenges and coping strategies adopted by nursing students during this pandemic situation. The research design adopted was embedded design. The conceptual framework for this study was based on modified Irvin Rosen Stock’s health belief and personal health behavioural model, 1966. The study has been conducted in selected nursing educational institutes. Non-probability Consecutive sampling technique has been adopted to select the desired sample. The total sample size was 324. The data was collected through semi-structured questionnaire. A depression scale was also used. The data was collected online through Google Forms. The collected data were analyzed by using both descriptive and inferential statistical methods. Our research found that Challenges faced by nursing students included maintaining the status of health, showing resistance to illness, dealing with stress, anxiety and depression related to health as well as academic disruption. Coping strategies adopted were watching news channels related to COVID-19, indulging in preventive behaviours such as washing hands, Health education to family members, and engaging in different forms of diversional activities such as prayer, exercise etc. Students also got adapted to online classes. This study, it is indicated that the Covid-19 pandemic has made a significant impact on Nursing students’; it poses various challenges which is dealt with student by various coping strategies.